The extent and magnitude of formalin adulteration in fish sold in domestic markets of Bangladesh: A literature review - Rabiul, Ahasan; Sayeeda, Rahman; Md Anwarul Azim, Majumder (Blackwell Publishing Ltd, 2016)
Bangladesh has been suffering from rampant food adulteration for the last few decades. Dishonest businessmen use formalin illegally as preservative to prevent spoilage and increase shelf-life of fish. Prolonged consumption of formalin adulterated fish may cause serious health hazards (i.e. cancers) which lead to increased morbidity and mortality. The aim of the review was to examine the extent and magnitude of illegal formalin treatment in fish sold in domestic markets of Bangladesh. A systematic review was conducted using conventional databases and non-conventional approaches to identify the relevant studies. Out of nine studies, eight confirmed the presence of formalin in fish collected from the markets of four main cities. Large and imported fishes were found to be mainly affected. Formalin adulterated fish was reported in seven studies. The fish were tested using a locally developed kit, and the amount of formalin treated fish ranged between 0.5 and 50%. Two other studies used the spectrophotometric method and reported specific formalin levels. The study conducted in Dhaka found mean levels of formalin to be 402.35 mg/kg in imported fishes and 118.60 mg/kg in local fishes which were much higher than the WHO recommended levels. In another study conducted in Mymensingh, formalin levels ranged between 1.4 and 7.3 mg/kg in both marketed and freshly caught pond fishes. The use of accurate, simple, specific and sensitive techniques is therefore highly recommended. The government and other agencies should address the issue as a priority basis by formulating effective policies and programs to safeguard the health of the public.